The Effect of Running Dictation Method on Students’ Listening Comprehension - Erwin Gay (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2021)
Listening is one of the challenging skills for EFL students. The teachers should apply the appropriate method or technique to improve students listening comprehension. The research aimed to determine whether or not there was a significant improvement in students’ listening achievement after being taught by running dictation method. The sample of this research was 20 of the second-grade students of SMA Negeri 1 Sulabesi Tengah consisting of 9 males and 11 females. The method of this study was an experimental study with a one-group pretest and posttest design. The data were collected using students' results in listening comprehension pretest and posttest. T-test was used to analyze the data. The data show that teaching listening skills through running dictation has positively influenced students’ performance. It is known from the mean of Pre-test’s score ∑x= 803 then increase to ∑y= 1,409 after applying running dictation method in the class. The result of the statistical analysis in the research showed the value of is higher than (=5,957 means that the zero Hypothesis ( ) is rejected and the Alternative Hypothesis ( ). Keywords: Running Dictation, method, listening skill